Impact of the introduction of percutaneous edge-to-edge mitral valve reconstruction on clinical practice in Germany compared to surgical valve repair - Frankenstein, Lutz; Kaier, Klaus; Katus, Hugo; Bode, Christoph; Wengenmayer, Tobias; Zur Mühlen, Constantin von; Bekeredjian, Raffi; Täger, Tobias; Zehender, Manfred Karl-Heinz; Fröhlich, Hanna; Stachon, Peter (Clinical research in cardiology, 2021)
The introduction of percutaneous mitral valve (MV) repair had an effect on clinical practice in comparison with surgical MV repair. Complete nationwide data are useful in examining how the introduction of a new technique influences clinical practice.